Migration‐tracking integrated phylogeography supports long‐distance dispersal‐driven divergence for a migratory bird species in the Japanese archipelago. Issue 11 (2nd May 2021) - Aoki, Daisuke; Sakamoto, Haruna; Kitazawa, Munehiro; Kryukov, Alexey P.; Takagi, Masaoki
Abstract: Long‐distance dispersal (LDD) outside a species' breeding range contributes to genetic divergence. Previous phylogeographic studies of migratory bird species have not discriminated LDD from vicariant speciation in their diversification process. We conducted an integrative phylogeographic approach to test the LDD hypothesis, which predicts that a Japanese migratory bird subspecies diverged from a population in the coastal region of the East China Sea (CRECS) via LDD over the East China Sea (ECS). Haplotype networks of both mitochondrial and nuclear genes of its three subspecies were reconstructed to examine whether the Japanese subspecies of the Brown Shrike ( Lanius cristatus superciliosus ) diverged from an ancestral CRECS population. A species distribution model (SDM) for the Japanese subspecies was constructed using bioclimatic variables under the maximum entropy algorithm. It was projected backwards to the climate of the last glacial maximum (LGM) to infer the candidate source area of colonization. A migratory route of L. c. superciliosus, which possibly reflects a candidate past colonization route, was tracked by light‐level geolocators. Molecular phylogenetic networks suggest that the Japanese subspecies diverged from a population in the CRECS and maintained anciently diverged haplotypes. The SDM inferred that the emerged continental shelf of the ECS and the present CRECS were suitable breeding areas for the Japanese subspecies during the LGM. A major migratory route for L. c. superciliosus was inferred between the CRECS and the Japanese archipelago across the ECS. Our integrative approach supported the LDD hypothesis for divergence of the Japanese subspecies of the Brown Shrike. Shrinkage of the ECS may have been responsible for successful population establishment, due to a sufficient number of migrants overshooting to the Japanese archipelago from the CRECS. Our framework provides a new phylogeographic scenario for this region. Discriminating LDD and vicariance models helps improve our understanding of the phylogeographic histories of migratory species. Abstract : We present a hypothetical phylogeographic scenario of divergence of a migratory bird species, the Brown Shrike in East Asia. A new scenario was proposed by integrative phylogeography including migration tracking and species distribution modeling. Long‐distance dispersal may have been important for its diversification process.